Transcribing whole-body sense-making by non-dominant students in multilingual classrooms. Issue 4 (2nd October 2021) - Tyler, Robyn
ABSTRACT: Whole-body sense-making offers insights for the analysis of identity work in learning in multilingual classroom contexts. The concept has the potential to draw together two strands of classroom discourse scholarship, namely multilingual and multimodal discourse studies. The data presented in this paper constitutes a moment of whole-body sense-making in Science learning in a multilingual South African high school in which the key participant meshes language and identity positions to appropriate Science discourse. The paper tracks the transcription of this moment and the production of a comic strip as transvisual in order to provide a metamethodological discussion of transcription practices linked to a specific research study. Technical and epistemological concerns about translation of speech by speakers of non-dominant languages as well as multimodality in transcription of classroom discourse are explored from a decolonial perspective. The affordances and limitations of the comic strip in representing the agency and voice of non-dominant youth in whole-body sense-making are outlined.